Exploring the Gut-Brain Axis: Gut Microbiome Influence on Immune-Mediated Movement Disorderse-Mediated Movement Disorders - Astrid Ekklesia Saputri; Muhammad Naufal Al-Firas; Muhammad Naufa Anwar; Rian Ka Praja (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
In recent years, there has been substantial growth in research concerning the gut microbiome, largely due to its recognized role in influencing human physiology and immune function. The microbiome represents a complex ecosystem that interacts with infections, potentially shaping host responses along the gut-brain axis and impacting health outcomes. Imbalances in gut microbiota have been linked to various neurodegenerative diseases, including multiple sclerosis, Guillain-Barré syndrome, and autoimmune encephalitis. This bibliometric study aimed to deepen our understanding of the relationship between gut microbiota and immune-mediated movement disorders, addressing gaps in research knowledge and investigating underlying mechanisms. Through an analysis of research themes, countries, institutions, and publication trends, we utilized the Scopus database and VOSviewer software to conduct a comprehensive examination. Our findings, spanning the years 2015 to 2023, revealed that the United States and Germany were leading contributors to global research in this area. Furthermore, Parkinson’s disease emerged as a prominent topic within the context of movement disorders associated with gut microbiota dysbiosis. Overall, this bibliometric analysis highlights the evolving landscape of gut microbiome research, emphasizing the need for continued exploration to inform preventive strategies and enhance infection management worldwide.